Effect of PEGylation on the activity and stability of horseradish peroxidase and l-N-carbamoylase in aqueous phases. Issue 9 (September 2015) - Hsieh, Yuan-Pang; Lin, Sung-Chyr
Graphical abstract: Highlights: Lysine residues of carbamoylase are more accessible for PEG than those of HRP. PEG-HRP showed enhanced activity due to reduction in radical-induced inactivation. PEG-HRP exhibited significantly higher storage stability than unpegylated HRP. PEG-carbamoylase exhibited lower activity due to higher mass transfer resistance. Extent of carbamoylase activity repression increased with the level of pegylation. Abstract: Effect of pegylation on the activities and stabilities of horseradish peroxidase (HRP) and n -carbamoyl- l -amino acid amidohydrolase (l - N -carbamoylase) was investigated. Pegylation was favored under alkaline conditions with high PEG/enzyme molar ratios. The lysine residues in l - N -carbamoylase were found to be more readily accessible for pegylation than those in HRP, leading to the formation of multi-pegylated enzymes. Pegylation and addition of mPEG as an additive improved HRP activity by 64% and 42%, respectively, via the formation of protective layers against the free radical-induced inactivation. The activity of pegylated l - N -carbamoylase, however, declined due to the additional mass transfer resistance introduced by the PEG layers. The extent of reduction in l - N -carbamoylase activity increased with the level of pegylation. In terms of thermostability, both the addition of mPEG as an additive and pegylation with PEG5000 led to a decline in thermostability. Nevertheless, pegylation of HRP with PEG2000 resulted in a PEG-HRP conjugate exhibiting a thermostability two-fold that of the control at 70 °C, probably due to the capability of the relatively hydrophilic PEG domains on the conjugate in avoiding enzyme aggregation. After a 4-day incubation at room temperature, pegylated HRP retained significantly higher activity, 89%, than the control, 12%.